2021
DOI: 10.3168/jds.2021-20477
|View full text |Cite
|
Sign up to set email alerts
|

Milk metabolome reveals variations on enteric methane emissions from dairy cows fed a specific inhibitor of the methanogenesis pathway

Abstract: Metabolome profiling in biological fluids is an interesting approach for exploring markers of methane emissions in ruminants. In this study, a multiplatform metabolomics approach was used for investigating changes in milk metabolic profiles related to methanogenesis in dairy cows. For this purpose, 25 primiparous Holstein cows at similar lactation stage were fed the same diet supplemented with (treated, n = 12) or without (control, n = 13) a specific antimethanogenic additive that reduced enteric methane produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 74 publications
(91 reference statements)
0
3
0
Order By: Relevance
“…It was found that the alanine pathway was the center of interactions of many other pathways [49], which implied the activation of this pathway might be related to higher methane emissions. It is reported that Arginine and proline metabolism (detected in Angus and KC population) and Phenylalanine metabolism (detected in KC population) were significantly affected pathway on enteric methane emissions from dairy cows [50].…”
Section: Plos Onementioning
confidence: 98%
“…It was found that the alanine pathway was the center of interactions of many other pathways [49], which implied the activation of this pathway might be related to higher methane emissions. It is reported that Arginine and proline metabolism (detected in Angus and KC population) and Phenylalanine metabolism (detected in KC population) were significantly affected pathway on enteric methane emissions from dairy cows [50].…”
Section: Plos Onementioning
confidence: 98%
“…The quest for alternate measures of enteric methane emissions has broadened to include substances found in living organisms, including fatty acids (FAs) in milk [ 113 ]. Milk FAs show enormous potential as a methane proxy due to their direct correlation with microbial digestion in the rumen.…”
Section: Milk Production and Compositionmentioning
confidence: 99%
“…Both C15:0 and C17:0 were positively correlated with CH 4 [ 90 , 91 , 92 ]. It has been shown that OBCFAs produced by rumen microbial activity, such as iso -C14, iso -C15, iso -C16, and C23:0, are reduced by a specific anti-methanogenic additive that lowers enteric methane production [ 93 ]. Furthermore, the concentration of VFA in the rumen can be related to methane emissions, indicating that analyzing OBCFA in ruminant milk could help determine CH 4 emissions [ 9 ], which can be used in the future to reduce the negative impact of cattle farming on the environment.…”
Section: Obcfas As a Biomarker Of Rumen Fermentationmentioning
confidence: 99%